Step
*
of Lemma
rsum-of-nonneg-zero-iff
∀[n,m:ℤ]. ∀[x:{n..m + 1-} ⟶ ℝ].
  uiff(Σ{x[i] | n≤i≤m} = r0;∀i:{n..m + 1-}. (x[i] = r0)) supposing ∀i:{n..m + 1-}. (r0 ≤ x[i])
BY
{ Auto }
1
1. n : ℤ
2. m : ℤ
3. x : {n..m + 1-} ⟶ ℝ
4. ∀i:{n..m + 1-}. (r0 ≤ x[i])
5. Σ{x[i] | n≤i≤m} = r0
6. i : {n..m + 1-}
⊢ x[i] = r0
2
1. n : ℤ
2. m : ℤ
3. x : {n..m + 1-} ⟶ ℝ
4. ∀i:{n..m + 1-}. (r0 ≤ x[i])
5. ∀i:{n..m + 1-}. (x[i] = r0)
⊢ Σ{x[i] | n≤i≤m} = r0
Latex:
Latex:
\mforall{}[n,m:\mBbbZ{}].  \mforall{}[x:\{n..m  +  1\msupminus{}\}  {}\mrightarrow{}  \mBbbR{}].
    uiff(\mSigma{}\{x[i]  |  n\mleq{}i\mleq{}m\}  =  r0;\mforall{}i:\{n..m  +  1\msupminus{}\}.  (x[i]  =  r0))  supposing  \mforall{}i:\{n..m  +  1\msupminus{}\}.  (r0  \mleq{}  x[i])
By
Latex:
Auto
Home
Index